Problems of teaching Tuvan as foreign language to Turkish students - Zhazira Otyzbay (Novye Issledovaniâ Tuvy, 2018)
Tuvan and Turkish are cognate languages. Although they haven’t been in direct contact for thousands of years, they have preserved common features on all levels of linguistic structure. At the same time, a number of dissimilarities have accumulated over time, which makes it difficult and time-consuming for Turkish students to learn it. At the moment, a number of Turkish universities have departments of modern Turkic languages and literatures which offer courses and programs in various languages, including Tuvan.